Damping robot's head movements affects human-robot interaction - Gibert, Guillaume; Lance, Florian; Petit, Maxime; Pointeau, Gregoire; Dominey, Peter Ford (HRI '14 : proceedings of the 2014 ACM/IEEE International Conference on Human-Robot Interaction : March 3-6, 2014, Bielefeld, Germany, 2014)
A new research platform has been developed to study human-robot interaction and communication. In this setup, a humanoid robot is used as a proxy between two humans involved in dyadic interactions. An experimenter is bound with a humanoid robot. He can control in real-time and sensor free the eye and face/head movements performed by a humanoid robot with his own movements. The experimenter can perceive the scene as if he was the robot. Manipulations can be applied in real-time to any movement leaving the rest of the dynamics untouched. For instance, we have started investigating the effect of damping head movements during dyadic interaction. Preliminary results show that naive subjects' head nods increase when attenuation was applied on the robot's head movements.